Victims’ Participation According to the Jurisprudence of the International Criminal Court (2011)
The role accorded to victims in the ICC proceedings is considered as one of the most significant features of the Rome Statute. It is acknowledged that the interests of victims often differ from the interests of the Prosecution, which is primarily responsible for ensuring that the interests of the society are protected. However, during the negotiation of the Rome Statue the idea that victims should be conferred upon procedural rights gained increasing support as reflecting an international human rights' tendency. The Statute contains only a few prescriptions defining the notion of 'victim' and establishing the rights they are empowered to exercise. Nonetheless, extensive ICC jurisprudence has already ruled on several controversial issues which are of utmost relevance for shaping such a role. This article analyzes and systematizes this jurisprudence and it examines the meaning of victims' participation before a Court created to surrogate inactive States.